2018
DOI: 10.4103/jets.jets_33_17
|View full text |Cite
|
Sign up to set email alerts
|

Amitraz poisoning: The (Un) common poisoning

Abstract: Pesticide poisoning is always a clinical conundrum for the emergency physician (EP), the complexity of which increases when the pesticide has no antidote! Over the past decade, there has been a sharp increase in cases of Amitraz poisoning, a pesticide routinely used in veterinary medicine, available without a prescription. The usual presentation includes bradycardia, hypotension, poor sensorium, and miosis. In the absence of accurate history, these clinical features can be confused with the cholinergic toxidro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…There was no history of ataxia, nystagmus or convulsions. Ataxia and coma have also been attributed to solvents used for [1][2][3][4][5][6] example Xylene . Our patient's coma lasted for 36 hours, however, other studies have shown that CNS 3 depression ranged from a few hours to 24 hours .…”
Section: Table 1: Results Of the Initially Ordered Laboratory Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no history of ataxia, nystagmus or convulsions. Ataxia and coma have also been attributed to solvents used for [1][2][3][4][5][6] example Xylene . Our patient's coma lasted for 36 hours, however, other studies have shown that CNS 3 depression ranged from a few hours to 24 hours .…”
Section: Table 1: Results Of the Initially Ordered Laboratory Testsmentioning
confidence: 99%
“…Amitraz is normally sold as a 12.5 to 50% formulation dissolved in an organic solvent mostly 1,5 Xylene . It is used as an ectoparasite to control Demodicosis in canines, ticks and mites in cattle and sheep, Psylla in pears and also Red Spider infection [1][2][3][4][5][6] in fruit crops . Human exposure can be intentional or accidental via inhalation, skin contact or 1,4 ingestion .…”
Section: Introductionmentioning
confidence: 99%
“…Since there are no randomized trials, no conclusions can be drawn on the ideal management strategy for this poisoning. [63][64][65][66][67][68][69][70][71][72][73][74] conclusIon Amitraz poisoning occurs in either accidental or suicidal manner and is more common in children than adults. Majority of the cases have been reported from Turkey, though there has been a recent rise in the number of cases reported from South Africa and India.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the inhibition of acetylcholinesterase (AChE) by OP insecticides, such as fenitrothion and malathion, causes the accumulation of acetylcholine (ACh), and leads to the overstimulation of the muscarinic receptors that induces miosis [2,4]. Although patients' pupils were miotic (1-2 mm) in clinical emergency cases of OP poisonings [5,6], in forensic autopsy cases, miosis was not always been observed owing to the elapsed time after death [7][8][9]. Conversely, the serum cholinesterase (ChE) activity markedly decreased in cases of fatal OP poisonings [7][8][9]; thus, the measurement of the deceased's serum ChE levels is used to determine the direct cause of death in acute poisoning cases caused by the ingestion of OPs [10].…”
Section: Introductionmentioning
confidence: 99%